Five crew, how many clergy : pourquoi certains noms collectifs peuvent-ils servir à nommer des membres ? - Laure Gardelle (Anglophonia)
A collective noun is typically defined as a noun which, in the singular, involves a plurality of members (e.g. (a) crew). But some of these nouns can also denote members, when they are used as uninflected plurals (e.g. these crew); some of them even license the numeral one (e.g. one crew, meaning one member of crew). The present paper focuses on these plural uses, which have not been much studied to date, and which also involve non-count nouns that denote collective supercategories (e.g. (these) livestock). The paper first describes the data from two corpora of American English. It then shows that these uses are not collective: what the noun denotes is members of a class (e.g. for crew, of a professional category), and at the same time, the fact that these members are typically construed as part of a group. For the nouns that are originally count collectives, the uninflected plural implies a change of denotation, from a whole to members of a professional category. For the nouns that denote collective supercategories, the plural merely gives more salience to the units that compose the whole. What the two cases have in common is that the units are hardly individuated: they are defined by the class to which they belong, that is, with a plurality as a starting point. Consequently, two police, for instance, is not always interchangeable with two policemen. The paper finally looks for a term for these uses. Internal plural is rejected in favour of aggregate.